Haiti - monetary policy in the context of a large foreign capital flows - Rosemond, Edgard (Central Bank of Barbados [Bridgetown]BB, 1992)
Presents, analyzes and criticizes the economic framework of Haiti's monetary policy during the 1980s emphasizing the monetary and fiscal policy of two particular years (1986 and 1987) which achieved satisfactory results in the areas of inflation budget deficit reduction and balance of payments viability.